Bloodstream infections in patients with rectal colonization by Klebsiella pneumoniae producing different type of carbapenemases: a prospective, cohort study (CHIMERA study). (February 2022) - Falcone, Marco; Tiseo, Giusy; Galfo, Valentina; Giordano, Cesira; Leonildi, Alessandro; Marciano, Emanuele; De Simone, Paolo; Biancofiore, Giandomenico; Boggi, Ugo; Barnini, Simona; Menichetti, Francesco; ,
Abstract: Objective: To investigate the hypothesis that intestinal colonization by different types of carbapenemase-resistant Klebsiella pneumoniae (CR-Kp) leads to different risks for bloodstream infections (BSI) caused by the same colonizing organism. Methods: Prospective observational study including consecutive CR-Kp rectal carriers admitted to the Pisa University Hospital (December 2018 to December 2019). Patients underwent rectal swabbing with molecular testing for the different carbapenemases at hospital admission and during hospitalization. Rectal carriers were classified as: NDM, KPC, VIM and OXA-48. The primary end point was the rate of BSI by the same colonizing organism in each study group. A multivariate logistic regression analysis was performed to identify factors independently associated with the risk for BSI by the colonizing organism. Results: Of 677 rectal carriers, 382/677 (56.4%) were colonized by NDM, 247/677 (36.5%) by KPC, 39/677 (5.8%) by VIM and 9/677 (1.3%) by OXA-48. Dissemination of NDM-Kp was mostly sustained by ST147, while KPC-Kp belonged to ST512. A higher rate of BSI was documented in NDM rectal carriers compared with KPC rectal carriers (59/382, 15.4% versus 20/247, 8.1%, p 0.004). Incidence rates of BSI per 100 patients/month were significantly higher in the NDM group (22.33, 95% CI 17.26–28.88) than in the KPC group (9.56, 95% CI 6.17–14.82). On multivariate analysis, multi-site extraintestinal colonization, solid organ transplantation, invasive procedures, intravascular device, admission to intensive care unit, cephalosporin, fluoroquinolones and NDM rectal colonization (OR 3.27, 95% CI 1.73–6.18, p < 0.001) were independently associated with BSI. Conclusions: NDM-Kp was associated with increased risk of BSI compared with KPC-Kp. This finding seems to be strongly related to the high-risk clone ST147.